2016
DOI: 10.1542/hpeds.2016-0049
|View full text |Cite
|
Sign up to set email alerts
|

Infant Videofluoroscopic Swallow Study Testing, Swallowing Interventions, and Future Acute Respiratory Illness

Abstract: OBJECTIVES: Tube feedings are commonly prescribed to infants with swallowing abnormalities detected by videofluoroscopic swallow study (VFSS), but there are no studies demonstrating efficacy of these interventions to reduce risk of acute respiratory illness (ARI). We sought to measure the association between swallowing interventions and future ARI, among VFSS-tested infants. METHODS: Retrospective cohort of all infants (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Jackson showed symptom improvements from feeding interventions in a population of Down syndrome patients with aspiration (30). Coon questioned the benefits of thickening for oropharyngeal dysphagia patients but found decreased acute respiratory hospitalizations for children with silent aspiration that received thickening (31). Khoshoo showed that thickening decreased the occurrence of aspiration in a small group of infants with swallowing dysfunction associated with bronchiolitis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Jackson showed symptom improvements from feeding interventions in a population of Down syndrome patients with aspiration (30). Coon questioned the benefits of thickening for oropharyngeal dysphagia patients but found decreased acute respiratory hospitalizations for children with silent aspiration that received thickening (31). Khoshoo showed that thickening decreased the occurrence of aspiration in a small group of infants with swallowing dysfunction associated with bronchiolitis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have examined the presentation and epidemiology of swallowing dysfunction in young children; this remains both an under-studied and under-appreciated area in clinical pediatrics and the prevalence of oropharyngeal dysphagia appears to be increasing due to increased survival of premature infants and other children with chronic medical problems 2, 28, 29 . We focused our study on infants and children under age 2 because this group has the highest rate of oropharyngeal dysphagia of any pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both children and adults have shown that thicker liquids alter the temporal characteristics of swallowing, especially closure of the true vocal cords, and lengthen deglutition time (63, 64). In a retrospective study of 546 infants, children with silent aspiration had fewer acute respiratory infections requiring admission or emergency room visits when receiving thickened feeds than those without thickening (65). In a study of 15 infants with respiratory syncytial virus bronchiolitis, 9 were found to have abnormal VFSS studies (laryngeal or tracheal penetration or aspiration) with thin barium.…”
Section: Management Of Oropharyngeal Dysphagia-associated Feeding Difmentioning
confidence: 99%